Prophylactic Avoidance of Hazardous Prey by the Ant Host Myrmica rubra - Pereira, Hugo (Insects, 2020)
Ants are the hosts of many microorganisms, including pathogens that are incidentally brought inside the nest by foragers. This is particularly true for scavenging species, which collect hazardous food such as dead insects. Foragers limit sanitary risks by not retrieving highly infectious prey releasing entomopathogenic fungal spores. This study investigates whether similar prophylactic strategies are also developed for food associated with weak or delayed risks of fungal contamination. We compared, in Myrmica rubra ant colonies, the retrieval dynamics of dead flies that were (1) conidia-free, (2) covered with a low amount of Metarhizium brunneum entomopathogenic conidia or (3) recently fungus-killed but not yet sporulating. Foragers mostly avoided fungus-killed prey and delayed the retrieval of conidia-covered flies. A second sanitary filter occurred inside the nest through a careful inspection of the retrieved prey. Ultimately, ants mostly consumed conidia-free and conidia-covered flies, but they relocated and discarded all fungus-killed prey outside of the nest. Our study confirms that, as a host of generalist entomopathogenic fungi, Myrmica rubra ants have developed a prophylactic avoidance and a differential management of prey depending on their infectious potential. We discuss the functional value as well as the possible cues underlying pathogen avoidance and prey discrimination in ants.